2021
DOI: 10.1093/infdis/jiab186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delaying Antiretroviral Treatment During Primary Human Immunodeficiency Virus Infection on Telomere Length

Abstract: Background Telomere length (TL) shortens during aging, HIV-seroconversion and untreated chronic HIV infection. It is unknown whether early antiretroviral therapy (ART) start is associated with less TL shortening during primary HIV infection (PHI). Methods We measured TL in peripheral blood mononuclear cells by quantitative PCR in participants of the Zurich PHI Study with samples available for >6 years. We obtained uni-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
6
1
Order By: Relevance
“…Prior evidence has suggested that TL is shorter in PWH compared to the general population. Our study confirms and extends previous reports by others [17,18] and us [19] that have shown significant TL decline occurring during HIV seroconversion [17,18], with ART initiation delay during primary HIV infection [19], and during untreated or suboptimally treated chronic HIV infection [33].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior evidence has suggested that TL is shorter in PWH compared to the general population. Our study confirms and extends previous reports by others [17,18] and us [19] that have shown significant TL decline occurring during HIV seroconversion [17,18], with ART initiation delay during primary HIV infection [19], and during untreated or suboptimally treated chronic HIV infection [33].…”
Section: Discussionsupporting
confidence: 92%
“…A 2.12% annual TL decline during untreated HIV might translate into 11% shorter TL over 5 years. This compares to 8.2% shorter TL (the effect of being 10 years older) and 17%-22% shorter TL (the effect of delayed ART start during primary HIV infection) in our previous study in Swiss PWH [19]. In addition, a 2.8-fold shorter TL was associated with an approximately twofold increased coronary artery disease event risk in Swiss PWH [3].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“… 63 This positive effect of ART on TL, diminishes when ART initiation is delayed. 64 Likely, this deceleration in TL recovery despite successful ART is hampered by the extension of initial damage. The ART benefit on TL is maintained in long-term treated aviremic HIV-infected adults, although more longitudinal studies are needed to confirm it.…”
Section: Molecular and Cellular Biomarkers In Hiv Ageingmentioning
confidence: 99%